Modification of heparanase gene expression in response to conditioning and LPS treatment: strong correlation to rs4693608 SNP. Issue 4 (6th December 2013) - Ostrovsky, Olga; Shimoni, Avichai; Baryakh, Polina; Morgulis, Yan; Mayorov, Margarita; Beider, Katia; Shteingauz, Anna; Ilan, Neta; Vlodavsky, Israel; Nagler, Arnon
Abstract : Heparanase rs4693608 SNP discrepancy between recipients and donors correlates with post transplantation engraftment and risk of acute GVHD. Abstract: Heparanase is an endo-β-glucuronidase that specifically cleaves the saccharide chains of HSPGs, important structural and functional components of the ECM. Cleavage of HS leads to loss of the structural integrity of the ECM and release of HS-bound cytokines, chemokines, and bioactive angiogenic- and growth-promoting factors. Our previous study revealed a highly significant correlation of HPSE gene SNPs rs4693608 and rs4364254 and their combination with the risk of developing GVHD. We now demonstrate that HPSE is up-regulated in response to pretransplantation conditioning, followed by a gradual decrease thereafter. Expression of heparanase correlated with the rs4693608 HPSE SNP before and after conditioning. Moreover, a positive correlation was found between recipient and donor rs4693608 SNP discrepancy and the time of neutrophil and platelet recovery. Similarly, the discrepancy in rs4693608 HPSE SNP between recipients and donors was found to be a more significant factor for the risk of aGVHD than patient genotype. The rs4693608 SNP also affected HPSE gene expression in LPS-treated MNCs from PB and CB. Possessors of the AA genotype exhibited up-regulation of heparanase with a high ratio in the LPS-treated MNCs, whereas individuals with genotype GG showed down-regulation or no effect on HPSE gene expression. HPSE up-regulation was mediated by TLR4. The study emphasizes the importance of rs4693608 SNP for HPSE gene expression in activated MNCs, indicating a role in allogeneic stem cell transplantation, including postconditioning, engraftment, and GVHD.